The humanity project [large type] - Thompson, Jean, 1950- (Thorndike Press, 2013)
After surviving a shooting at her high school, Linnea is sent to live with her estranged father, Art. Art's neighbor, Christie, is a nurse whose eccentric patient, Mrs. Foster, has given her the reins of the Humanity Project, a bizarre and well-endowed charity fund. Conner, the Fosters' handyman, has become the one person Linnea can confide in. As these characters hurtle toward their fates, the Humanity Project is born: Can you pay someone to be good?